EFFECT OF LIME AND PHOSPHORUS ON YIELD AND NUTRIENTS UPTAKE BY MAIZE IN MOUNTAIN ACIDIC SOIL OF HIMACAHAL PRADESH - DIXIT, S.P. (Annals of Agricultural Research, 2014)
A field experiment was conducted in maize-radish-onion cropping sequence. There were three levels of lime viz. 0, 1.54 and 0.08 t/ha (full lime requirement) and four levels of P viz. 0,13,26 and 39 kg/ha replicated three times. The results revealed that lime application significantly increased the yield of maize grain up to 3.08t/ha during both the years and stover duing second year. This increase in grain yield due to half and full lime requirement was 17 and 23 per cent during 1999 and 9 and 21 per cent during 2000 over no lime dose, respectively. During first year of the experimentation, the significant increase in grain yield was up to 39 Kg P/ha. However, during 2000, the response narrowed down to 13 Kg/ha. The per cent increase over no P dose was 13, 24 and 29 and 10, 18 and 24 per cent due to 13, 26 and 39 kg/ha during first and second year, respectively. The response of P on stover yield of maize was significant up to 26 Kg P/ha during both the years. Uptake of N, P and K by maize grain as well as stover increased significantly due to each level of lime up to 30.8t/ha and P up to 39 kg/ha except during first year in P uptake by grain, where increase was up to 26 kg P/ha and K uptake where lime effect was up to half of the requirement instead of full dose.